FRI0356 Studies on Ageing and the Severity of Radiographic Joint Damage in Rheumatoid Arthritis. (9th June 2015) - Mangnus, L.; van Steenbergen, H.W.; Lindqvist, E.; Brouwer, E.; Reijnierse, M.; Huizinga, T.W.; Gregersen, P.K.; Berglin, E.; Rantapää-Dahlqvist, S.; van der Heijde, D.; van der Helm-van Mil, A.H.
Abstract : Background: The western population is ageing. It is unknown whether age at diagnosis affects the severity of Rheumatoid Arthritis (RA), we therefore performed the present study. Methods: 1, 875 RA-patients (7, 219 radiographs) included in five European and North-American cohorts (Leiden-EAC, Wichita, Umeå, Groningen and Lund) were studied on associations between age at diagnosis and joint damage severity. In 698 Leiden RA-patients with 7-years follow-up it was explored if symptom duration, anti-citrullinated-peptide-antibodies (ACPA), swollen joint count (SJC) and C-reactive-protein (CRP) mediated the association of age with joint damage. Fifty-six other RA-patients of the EAC-cohort underwent baseline MRIs of wrist, MCP and MTP-joints; MRI-inflammation (RAMRIS-synovitis plus bone marrow edema) was also evaluated in mediation analyses. Linear regression and multivariate normal regression models were used. Results: Analysis on the five cohorts and the Leiden-EAC separately revealed 1.026-fold and 1.034-fold increase of radiographic joint damage per year increase in age (β=1.026, 1.034, both p<0.001); this effect was present at baseline and constant over time. Age correlated stronger with baseline erosion-scores compared to joint space narrowing (JSN)-scores (r=0.38 versus 0.29). Symptom duration, ACPA, SJC and CRP did not mediate the association of age with joint damage severity. Age was significantly associated with the MRI-inflammation-score after adjusting for CRP and SJC (β=1.018, p=0.027). The association of age with joint damage (β=1.032, p=0.004) decreased after also including the MRI-inflammation-score (β=1.025, p=0.021), suggesting partial mediation. Conclusions: RA-patients presenting at higher age have more severe joint damage; this might be partially explained by more severe MRI-detected inflammation at higher age. Disclosure of Interest: None declared